CRISIS MANAGEMENT SYSTEM OF THE CREDIT ORGANIZATION ON THE BASIS OF THE MACROECONOMICAL AND MICROECONOMICAL TOOLS RANGE. - A. S. Tarada (Real Economics Publishing House, 2014)
The article covers the question of the complex crisis management system construction of the credit organization on the basis of the microeconomical and macroeconomical management tools range. It contains the data referring the place and role of the tools in the crisis management system and the complex model of the crisis management with the united statistical entity is built.